The Barren Spatial In Frank Norris’s Mcteague: A Story Of San Franciso - R. Senthilkumar; Dr. R. Bharathi (Revista Electronica de Veterinaria, 2024)
This research paper tries to explore the nature of McTeague and Trina in Frank Norris’s novel McTeague: A Story of San Francisco. Norris is one of the most important American novelists and his writhing is dealt with naturalism. He depicts the vast, monstrous and the tragic life of McTeague and social degradation and psychological disintegration. McTeague deals with the barren space, class determinism, social deterioration, destruction of identity etc., This novel exhibit’s themes like destructive nature of desire, the corrupting influence of money and the impact of societal forces on individual lives, harsh realities of urban life, struggles of the working class, the deterministic forces that shape their destinies, pessimistic view of human nature, character trapped in a web of their own desire and circumstances, gritty atmosphere of the city and the moral decay he perceived in the society of his time. He explores the couple’s courtship between marriage and their subsequent decent into poverty and violence of jealousy and greed.